Trees description in the main square of Sao Jose do Rio Preto, Sao Paulo State, Brazil - Fernandes, Camila Junqueira [UNESP]; Ferraz, Marcos Vieira [UNESP]; Gimenes, Renata [UNESP]; Sajovic Pereira, Suzana Targanski [UNESP]; Lopes Pivetta, Kathia Fernandes [UNESP] (Soc Brasileira Floricultura & Plantas Ornamentais, 2018)
The knowledge of the flora existing in the cities is of great importance from the ecological and sustainable point of view, as well as being a premise for actions that provide greater safety, comfort and well-being for the population. The objective of this work was to perform an analysis of the composition, diversity and quality of the tree flora (trees and palms) existing in Rui Barbosa Square, Sao Jose do Rio Preto, Sao Paulo State. This square is considered the main place for its location, history and use, and is located in the central region, next to the Cathedral. The arboreal individuals present in the square were counted, identified and evaluated the height and circumference of the trunk at the height of the chest; were determined phytosociological descriptors, Shannon-Weaver index and observed qualitative aspects (stem-glass balance, general status of the specimen, phytosanity and presence of association with other organisms: insects, lichens, epiphytes or parasites). The floristic composition of Rui Barbosa Square, consisted of 15 botanical families, composed of 25 genera and 28 species, in a total of 103 individuals, among trees and palm trees. The most representative species was Dypsis lutescens, with a frequency of 20.39%. The Shannon-Weaver index, an indicator of diversity, was 2.77, showing that the square presents great floristic diversity. The majority (72.8%) of individuals is in a regular or poor state; 66.02% had some fungus symptoms; 12.62% present problems due to termite attack; mosses, lichens and epiphytes are present in 73.78% of the individuals in the square.
Keywords: urban trees; public squares; urban planning